A distributed stabilised clustering algorithm for large-scale wireless ad hoc networks. (13th February 2007) - Purtoosi, Reza; Taheri, Hassan; Mohammadi, Abbas; Foroozan, Foroohar
A new distributed clustering algorithm for wireless ad hoc networks is presented. This algorithm reconfigures the clusters to deal with the dynamic behaviour of the ad hoc networks. In the proposed algorithm, the stability of the generated clusters has been taken into account. The mobile nodes compete with each other to become cluster-head based on the number of neighbours and stability. A number of simulations have been conducted in some large-scale mobile networks to investigate the performance of this algorithm. The simulation results show scalability and stability advantage of this algorithm in networks with large number of mobile nodes.